Meningkatkan Hasil Belajar Pakat Melalui Model PBL pada Siswa SD Negeri Kutowinangun 08 Salatiga - Setiono Setiono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to determine the improvement of cognitive and affective learning outcomes in the dimensions of faith in God Almighty and Mutual Cooperation through the PBL model for students at SD Negeri Kutowinangun 08. This type of research is classroom action research with research steps including planning, implementation, observation, and reflection in each cycle. This study consists of two cycles. The research location is SD Negeri Kutowinangun 08 Salatiga, focusing on fourth-grade students with the material